System of Equations make a Trig Equation?

Geometry Level 3

If the planes 3 x + 2 y z = 4 3x+2y-z=4 , 2 x + y 3 z = 1 2x+y-3z=1 , and x sin θ + y cos θ 2 z = k x\sin{\theta}+y\cos{\theta}-2z=k meet at the same line, k k is a constant, θ \theta , x x , y y , and z z are real, then the sum of all possible values of k k can be expressed as a b -\frac{a}{b} , where a a and b b are coprime positive integers.

Submit your answer as 2 a + 2 b 2a+2b .


The answer is 254.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Yashas Ravi
Nov 7, 2019

Let A = 3 x + 2 y z = 4 A=3x+2y-z=4 and B = 2 x + y 3 z = 1 B=2x+y-3z=1 . Because the planes meet at the same line, the plane governed by the 3rd equation is a linear sum of Equations A and B. Multiplying A A by m m , B B by n n , and adding the equations yields ( 3 m + 2 n ) x + ( 2 m + n ) y + ( m 3 n ) z = ( 4 m + n ) = k (3m+2n)x+(2m+n)y+(-m-3n)z=(4m+n)=k . We can set 3 m + 2 n = sin θ 3m+2n=\sin{θ} , 2 m + n = cos θ 2m+n=\cos{θ} , and m + 3 n = 2 m+3n=2 . This means that m = 2 3 n m=2-3n , so 6 7 n = sin θ 6-7n=\sin{θ} and 4 5 n = cos θ 4-5n=\cos{θ} . By the Pythagorean Identity, ( 6 7 n ) 2 + ( 4 5 n ) 2 = 1 (6-7n)^2+(4-5n)^2=1 . Solving this yields 2 2 real values for n n , and by substitution, 2 2 real values for m m . Using Vieta's formulas, the sum of the 2 2 values of 4 m + n 4m+n comes out to be 90 37 \frac{-90}{37} and 2 ( 90 + 37 ) = 254 2(90+37)=254 which is the final answer.

David Vreken
Jan 27, 2021

Let z = t z = t .

Then 3 x + 2 y t = 4 6 x + 4 y 2 t = 8 3x + 2y - t = 4 \Longrightarrow 6x + 4y - 2t = 8

and 2 x + y 3 t = 1 6 x + 3 y 9 t = 3 2x + y - 3t = 1 \Longrightarrow 6x + 3y - 9t = 3 .

Subtracting these two equations give y + 7 t = 5 y = 5 7 t y + 7t = 5 \Longrightarrow y = 5 - 7t

Substituting y = 5 7 t y = 5 - 7t into 3 x + 2 y t = 4 3x + 2y - t = 4 gives 3 x + 2 ( 5 7 t ) t = 4 x = 2 + 5 t 3x + 2(5 - 7t) - t = 4 \Longrightarrow x = -2 + 5t .

Substituting x = 2 + 5 t x = -2 + 5t , y = 5 7 t y = 5 - 7t , and z = t z = t into x sin θ + y cos θ 2 z = k x \sin \theta + y \cos \theta - 2z = k gives ( 2 + 5 t ) sin θ + ( 5 7 t ) cos θ 2 t = k (-2 + 5t) \sin \theta + (5 - 7t) \cos \theta - 2t = k , which rearranges to k = 2 sin θ + 5 cos θ + ( 5 sin θ 7 cos θ 2 ) t k = -2 \sin \theta + 5 \cos \theta + (5 \sin \theta - 7 \cos \theta - 2)t .

Substituting cos θ = ± 1 sin 2 θ \cos \theta = \pm \sqrt{1 - \sin^2 \theta} gives k = 2 sin θ ± 5 1 sin 2 θ + ( 5 sin θ 1 sin 2 θ 2 ) t k = -2 \sin \theta \pm 5\sqrt{1 - \sin^2 \theta} + (5 \sin \theta \mp \sqrt{1 - \sin^2 \theta} - 2)t

For k k to be a constant, the coefficient of t t must be negative, so 5 sin θ 1 sin 2 θ 2 = 0 5 \sin \theta \mp \sqrt{1 - \sin^2 \theta} - 2 = 0 , which solves to sin θ = 5 2 ± 7 35 37 2 \sin \theta = \cfrac{5\sqrt{2} \pm 7 \sqrt{35}}{37\sqrt{2}} .

Substituting sin θ = 5 2 ± 7 35 37 2 \sin \theta = \cfrac{5\sqrt{2} \pm 7 \sqrt{35}}{37\sqrt{2}} into k = 2 sin θ ± 5 1 sin 2 θ k = -2 \sin \theta \pm 5\sqrt{1 - \sin^2 \theta} gives k = 90 + 11 70 74 k = \cfrac{-90 + 11\sqrt{70}}{74} and k = 90 11 70 74 k = \cfrac{-90 - 11\sqrt{70}}{74} , which has a sum of 90 37 -\cfrac{90}{37} .

Therefore, a = 90 a = 90 , b = 37 b = 37 , and 2 a + 2 b = 254 2a + 2b = \boxed{254} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...